2005
DOI: 10.1016/j.icesjms.2005.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The recreational fishery off Majorca Island (western Mediterranean): some implications for coastal resource management

Abstract: The sociology and habits of recreational anglers on the Island of Majorca (western Mediterranean) were evaluated using telephone and on-site surveys, as well as fishing logbooks and recreational fishing competitions. The recreational fishery is one of the island's main leisure activities, 5.14% of the population (37 265 people) participating. Enthusiasts tend to be mainly middle class (most anglers own boats moored at marinas), middle-aged males (90% male, mean age 46 ± 2 years). The most popular fishing metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
228
6
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(261 citation statements)
references
References 31 publications
20
228
6
7
Order By: Relevance
“…A fish assemblage including about 40 species inhabits the meadows of P. oceanica off the Balearic Archipelago (Massutí, 1965;Grau et al, 1993;Reñones et al, 1995), but only three species (C. julis, D. annularis and S. scriba) represent the bulk of the catch of the recreational fishery (Morales-Nin et al, 2005;this study). This is because most of these species (Gobidae, Gobiesocidae, Syngnathidae and most Labridae) have mouth gapes that are too small to be caught with the hooks regularly used in the fishery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A fish assemblage including about 40 species inhabits the meadows of P. oceanica off the Balearic Archipelago (Massutí, 1965;Grau et al, 1993;Reñones et al, 1995), but only three species (C. julis, D. annularis and S. scriba) represent the bulk of the catch of the recreational fishery (Morales-Nin et al, 2005;this study). This is because most of these species (Gobidae, Gobiesocidae, Syngnathidae and most Labridae) have mouth gapes that are too small to be caught with the hooks regularly used in the fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Pickett and Pawson (1994) assessed the relevance of recreational angling for a marine species in Europe for the first time and concluded that sport anglers generated half the total catch of sea bass (Dicentrarchus labrax) off the United Kingdom. More recently, Coll et al (2004) and Chavoin and Boudouresque (2004) demonstrated the role of recreational spearfishing in the depletion of large fish from Mediterranean rocky reefs and Morales-Nin et al (2005) pointed out that 31% of the annual fish production at trophic level 4 is removed from the coastal waters of Majorca Island (Balearic Archipelago, western Mediterranean) by sport fishing. However, information about the relevance of recreational fishing in the Mediterranean is still scarce and limited to rocky bottoms (Sánchez Lizaso et al, 2000;Francour et al, 2001 and references herein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite numerous calls for the importance of recreational fishing to have greater acknowledgement in fisheries management (Kearney et al 1996, Morales-Nin et al 2005, there remains a paucity of long-term data on recreational fisheries, their impacts, and social and economic importance (Lewin et al 2006). Recreational fishing may have similar impacts on fish stocks (Coll et al 2004) and ecosystems 55 (Lewin et al 2006) as commercial fishing and, in certain areas, can form a greater proportion of the total catch than the commercial harvest (Kearney et al 1996, McPhee et al 2002.…”
Section: Introduction 50mentioning
confidence: 99%
“…Recreational fishing may have similar impacts on fish stocks (Coll et al 2004) and ecosystems 55 (Lewin et al 2006) as commercial fishing and, in certain areas, can form a greater proportion of the total catch than the commercial harvest (Kearney et al 1996, McPhee et al 2002. Recreational fishing can play an important role in the social dynamics of communities (Finn and Loomis 2001, Henry and Lyle 2003, Morales-Nin et al 2005 and is a popular activity worldwide, for the provision of food (Burger 60 2002) and as a leisure activity (Henry and Lyle 2003). The capacity for fishers to change their behaviour at will, perhaps targeting an alternative species (Gentner 2004) or travelling further to fish (Arlinghaus 2005), determines that managers must consider potential changes in fisher behaviour when assessing the overall impact of a recreational management strategy on an ecosystem.…”
Section: Introduction 50mentioning
confidence: 99%